General chemistry - Yambao, Bernadette A. (Mutya Pub. House, 2006)
"Chemistry Laboratory Experiments were written for students of General Chemistry I and II. This is a revised chemistry laboratory manual bearing additional experiments for new chemistry students." on Preface.